Biomarker pada Kanker Payudara - Indriastuti, Endah; Nur Fitriani, Fatimah; Djunaidi, Anwar (Jurnal Biomedika dan Kesehatan, 2025)
Breast cancer is the leading cause of cancer-related death among women worldwide. A biomarker is a molecule in the body that signals an abnormal process or condition, such as cancer. Numerous studies have focused on biomarkers in breast cancer. Widely used biomarkers in clinical settings include estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor-2 (HER2), Ki67, carcinoembryonic antigen (CEA), and cancer antigen (Ca) 15-3. Currently, circulating tumor cells (CTCs) and genome sequencing are being researched and are expected to play significant roles in managing breast cancer patients. These biomarkers can be detected in various sample types, enabling detection tailored to different purposes. They are vital for diagnosis, classification, and selecting effective treatment strategies, including personalized and targeted therapies, as well as predicting treatment response and monitoring for disease recurrence. Understanding of breast cancer biomarkers has improved considerably over time. This knowledge should be applied effectively to enhance diagnosis accuracy and personalize treatment. This narrative review aims to summarize previously used breast cancer biomarkers and provide updates on those currently being developed to improve patient care and outcomes.